Intervensi Massage pada Bayi Hiperbilirubin dengan Fototerapi - Rajasa, Hyang Kinanti; Zubaidah, Zubaidah; Widyastuti, Rita Hadi (Journal of Telenursing (JOTING), 2024)
This study aims to get a comprehensive picture of massage interventions that reduce the value of bilirubin in infants with hyperbilirubin with phototherapy. The method used is the scoping review method. Search articles using several databases, namely: Medline (PubMed), cinahl (Ebsco), Scopus (Elsevier), and Science Direct with publication time of articles from January 2019 to December 2024. The results show that 7 articles support massage interventions to reduce the values of Bilirubin. There are variations in massage interventions that are carried out to reduce the value of bilirubin. Most articles showing massage are done 2 times a day, in the morning and evening with a duration of 15-20 minutes. The massage method used in the article Body Massage, Abdominal Massage, Massage, and Bathing, Massage Acupressure, and Massage. In conclusion, massage can reduce the value of bilirubin, by paying attention to the duration, frequency, and massage methods carried out. Keywords: Bilirubin, Hyper Bilirubin, Jaundice, Massage, Neonates